Malay short stories in the 19th century - Nik Muhamad Affendi, Nik Rafidah (American-Eurasian Network for Scientific Information, 2014)
This study focuses on the Malay stories collection which were found at KITLV (Koninklij Instituut Voor de Taal-Lan-en Volkenkunde or well known as the Institute of Royal Linguistic and East Hindia Dutch Anthropology) and the manuscripts at the main library in Leiden, Netherland. The study examines Malay stories collection from the perspective of community. The methodology uses the psychological approach by Maslow. Maslow stresses several principles like physiological need, guaranteed safety, love, self appreciation and self perfection. The results of the study showed that traditional Malay stories community whether concious or unconscious incorporated the psychological elements in the stories. Thus, it showed that human has distinctive needs in continuity of life.